2022
DOI: 10.3390/jcm11123250
|View full text |Cite
|
Sign up to set email alerts
|

Nitrates vs. Other Types of Vasodilators and Clinical Outcomes in Patients with Vasospastic Angina: A Propensity Score-Matched Analysis

Abstract: Although vasodilators are widely used in patients with vasospastic angina (VA), few studies have compared the long-term prognostic effects of different types of vasodilators. We investigated the long-term effects of vasodilators on clinical outcomes in VA patients according to the type of vasodilator used. Study data were obtained from a prospective multicenter registry that included patients who had symptoms suggestive of VA. Patients were classified into two groups according to use of nitrates (n = 239) or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…26 Several subsequent studies assessed the effects of nitrates on clinical outcomes in VSA patients, usually reporting increased or neutral risk of cardiovascular events compared with no nitrate therapy, as summarised in Table 1. [30][31][32][33][34][35] The lack of beneficial effects of nitrates on CAS-related events may be related to a loss of their vasodilator effects on constricted epicardial arteries due to the development of tolerance. 36 Furthermore, continuous exposure to nitrates may be associated with an impairment of endothelial function related to their release of nitric oxide molecules.…”
Section: Nitratesmentioning
confidence: 99%
“…26 Several subsequent studies assessed the effects of nitrates on clinical outcomes in VSA patients, usually reporting increased or neutral risk of cardiovascular events compared with no nitrate therapy, as summarised in Table 1. [30][31][32][33][34][35] The lack of beneficial effects of nitrates on CAS-related events may be related to a loss of their vasodilator effects on constricted epicardial arteries due to the development of tolerance. 36 Furthermore, continuous exposure to nitrates may be associated with an impairment of endothelial function related to their release of nitric oxide molecules.…”
Section: Nitratesmentioning
confidence: 99%
“…Teragawa et al [ 6 ] identified active smoking as a possible risk factor associated with the increase in the index of microcirculatory resistance (IMR) for patients who underwent an invasive microvascular vasodilatory function test, showing that IMR differed according to the coronary artery branches and types of coronary spasm. Kim et al [ 7 ] documented that the chronic use of nitrates in patients with vasospastic angina, relative to other types of vasodilators, such as nicorandil, was associated with an increased risk of adverse clinical outcomes in a prospective nationwide registry database.…”
mentioning
confidence: 99%